Sonication effects on ash removal from rice husk in pyrolysis - Nasihatul Alia Kamaruzaman (Penerbit Universiti Malaysia Perlis, 2011)
This study is an investigation on fast pyrolysis technology of rice husk to get the data of producing the bio-oil. The removal of ash is to increase the purity of bio-oil yield. The composition and particle size distribution of the untreated and treated rice husk were determined and its thermal degradation behavior was analysed by thermogravimetric analysis (TGA) and also derivative thermal gravimetric (DTG). CHONS process was used to determine the components of carbon, hydrogen, oxygen, nitrogen and sulphur in the samples. The untreated and treated rice husk with 50, 70 and 80 amplitudes of sonication process were used to determine the differences data in the experiment. For producing the bio-oil yield, it must proceed with the fast pyrolysis by using the R-301 Catatest Reactor System for 8 minutes of heating process with 450C and 2 minutes of cooling process with -4C. The result by using sonication process with 80 amplitudes for 4 hours produced 34.5% of bio-fuel yield.